2018
DOI: 10.1371/journal.pone.0201389
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake kinetics and speed-time correlates of modified 3-minute all-out shuttle running in soccer players

Abstract: How parameters derived from oxygen uptake kinetics relate to critical speed is not fully understood, and how such parameters relate to more sport-specific performances, such as shuttle running, has not been investigated. Therefore, the primary aims of the present student were to examine the kinetics during all-out linear and shuttle running and compare physiological variables of all-out running to variables measured during a graded exercise test (GXT). Fifteen male soccer players performed a graded exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The most common criterion used in the reviewed studies is that the highest VO 2 observed in the verification phase should not exceed 3% of the highest VO 2 obtained in the CPET. This threshold can be justified by the technical error of measurement and intra-individual biological variation associated with the determination of VO 2max [ 15 , 56 , 57 , 62 , 63 , 69 , 71 , 78 , 82 , 86 , 89 91 , 95 , 107 , 108 , 113 , 116 , 120 122 ]. The more restrictive value of ≤ 2% [ 97 , 110 ] and the less restrictive values of ≤ 5–5.5% [ 104 106 , 111 ] may also be appropriate for single or different-day variability.…”
Section: Discussionmentioning
confidence: 99%
“…The most common criterion used in the reviewed studies is that the highest VO 2 observed in the verification phase should not exceed 3% of the highest VO 2 obtained in the CPET. This threshold can be justified by the technical error of measurement and intra-individual biological variation associated with the determination of VO 2max [ 15 , 56 , 57 , 62 , 63 , 69 , 71 , 78 , 82 , 86 , 89 91 , 95 , 107 , 108 , 113 , 116 , 120 122 ]. The more restrictive value of ≤ 2% [ 97 , 110 ] and the less restrictive values of ≤ 5–5.5% [ 104 106 , 111 ] may also be appropriate for single or different-day variability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because the linear AOT is already used regularly for the evaluation of aerobic fitness (Kramer et al. ) and the derivation of CS and D′ parameters, it is pertinent to note that the bi‐exponential model presented provides additional information that can be captured and tracked longitudinally; thereby, complementing an already robust assessment method.…”
Section: Discussionmentioning
confidence: 99%
“…The shuttle-running 3MT could add to the capability of testing tactical professionals. The shuttle-running test was designed and validated for sports athletes such as soccer, ice hockey, rugby, and basketball [ 32 , 44 ]. Commonly, athletes perform acceleration, deacceleration, and direction changes at high intensity.…”
Section: Methods Of Critical Speed Testingmentioning
confidence: 99%